Determination of Cationic Degree for Cationic Polyacrylamide and Its Sludge Dewatering Properties - Sun, Yongjun; Zheng, Huaili; Teng2, Houkai; Guan, Qingqing; Wang3, Yili; Chen, Wei; Fan, Wei; Liao, Yong (Asian Journal of Chemistry, 2014)
P(AM-DAC-BA) was synthesized by ultraviolet initiation with acrylamide (AM), acryloyloxyethyl trimethyl ammonium chloride (DAC) and butyl acrylate (BA) as monomers and P(AM-DAC) was synthesized with acrylamide and acryloyloxyethyl trimethyl ammonium chloride. The polymer was characterized by Fourier transform infrared (FTIR) spectrum. Cationic degree of P(AM-DAC-BA) was determined by colloid titration and the optimum titration condition: the P(AM-DAC-BA) concentration of 1 × 10-5 - 5 × 10-5 g g-1, pH 2-3, titration rate of 0.0653-0.0719 mL s-1, addition of 2-3 drops of toluidine blue as indicator. The sludge dewatering performances of P(AM-DAC-BA) and P(AM-DAC) were also studied and both high solid content and low supernatant turbidity were achieved. The dewatering tests indicated that P(AM-DAC-BA) was better than P(AM-DAC) in sludge dewatering performance.